Microstructural constraints on complex thermal histories of refractory CAI-like objects in an amoeboid olivine aggregate from the ALHA77307 CO3.0 chondrite. (15th June 2016) - Han, Jangmi; Brearley, Adrian J.
Abstract: We have carried out a FIB/TEM study of refractory CAI-like objects in one AOA from the ALHA77307 CO3.0 chondrite. The CAI-like objects in the AOA consist of a zoned sequence with a spinel-rich core through an intergrowth layer of spinel and Al-Ti-rich diopside to a diopside rim. The spinel-rich core consists of polycrystalline aggregates of spinel and ±minor melilite showing equilibrated grain boundary textures. The intergrowth layer contains fine-grained diopside and spinel with minor anorthite with highly curved and embayed grain boundaries. The diopside rim consists of polycrystalline aggregates of diopside. The compositions of pyroxene change significantly outward from Al-Ti-rich diopside in contact with the spinel-rich core to Al-Ti-poor diopside next to the surrounding olivine of the AOA. Overall microstructural and chemical characteristics suggest that the spinel-rich core formed under equilibrium conditions whereas the intergrowth layer is the result of reactions that occurred under conditions that departed significantly from equilibrium. The remarkable changes in formation conditions of the CAI-like objects may have been achieved by transport and injection of refractory objects into a region of a partially-condensed, Ca, Ti-saturated gas which reacted with spinel and melilite to form Al-Ti-rich diopside. Crystallographically-oriented TiO2 nanoparticles decorate the grain boundaries between spinel grains and between spinel and Al-Ti-rich diopside grains. During the disequilibrium back-reaction of spinel with a partially-condensed, Ca, Ti-saturated gas, metastable TiO2 nanoparticles may have condensed by an epitaxial nucleation mechanism and grown on the surface of spinel. These TiO2 nanoparticles are disordered intergrowths of the two TiO2 polymorphs, anatase and rutile. These nanoparticles are inferred to have nucleated as anatase that underwent partial transformation into rutile. The local presence of the TiO2 nanoparticles and intergrowth of anatase and rutile imply that the disequilibrium back-reaction of spinel with the gas occurred on a short timescale, i.e., minutes to hours at maximum.